Analysis of Variation in Total Airborne Bacteria Concentration to Assess the Performance of Biological Safety Cabinets in Microbial Laboratories - Sung Ho Hwang; Hyun Hee Park; Chung Sik Yoon (Elsevier, 2014)
Background: The purpose of this study was to compare the concentration of total airborne bacteria (TAB) in biosafety cabinets (BSCs) at universities and hospital microbial laboratories to assess the performance of BSCs. Methods: TAB was determined by using the single-stage Anderson sampler (BioStage Viable Cascade Impactor). The samples were obtained three times (with the BSC turned off and the shield open; with the BSC turned off and the shield closed; and with the BSC tuned on and operating) from the areas in front of 11 BSCs. Results: TAB concentrations of accredited and nonaccredited BSCs were determined. No significant differences were observed in the TAB concentrations of the accredited BSCs and the nonaccredited BSCs for the areas outside the BSCs in the laboratories (p > 0.05). TAB concentrations for the BSCs sampled with the shield open and the instrument turned off showed differences based on the sampling site outside the BSC in each laboratory. Conclusion: These results imply that TAB concentration is not altered by the performance of the BSCs or TAB itself and/or concentration of TAB outside the BSC is not a good index of BSC performance.